2010
DOI: 10.1111/j.1744-313x.2010.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical case–control study on the association between mannose‐binding lectin and susceptibility to HIV‐1 infection among northern Han Chinese population

Abstract: Mannose-binding lectin (MBL) is a key molecule of the innate immune system and a competent to bind carbohydrates of a variety of microorganisms, resulting in complement activation and opsonophagocytosis against various pathogens. However, there is no systemic investigation on the MBL's role in innate immune responses against HIV-1 infection among northern Han Chinese. This study investigated the association between MBL and HIV-1 infection susceptibility among northern Han Chinese. A total of 91 HIV-1 infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
(98 reference statements)
1
9
0
1
Order By: Relevance
“…We found no association between presence of MBL2 structural variants and promoter variants with HIV infection, in accordance with other findings [ 38 , 90 ], in contrast to reports of significant associations [ 37 , 83 , 84 , 91 ]. Similar results to ours of no association between MBL2 polymorphism and HIV infection, reported in a Colombian population, were explained as being due to existence of redundant constitutive acquired immune defence systems that can complement or take up the innate defence functions provided by MBL, which are likely favoured under conditions of high pathogen exposure [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found no association between presence of MBL2 structural variants and promoter variants with HIV infection, in accordance with other findings [ 38 , 90 ], in contrast to reports of significant associations [ 37 , 83 , 84 , 91 ]. Similar results to ours of no association between MBL2 polymorphism and HIV infection, reported in a Colombian population, were explained as being due to existence of redundant constitutive acquired immune defence systems that can complement or take up the innate defence functions provided by MBL, which are likely favoured under conditions of high pathogen exposure [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study showed no difference in plasma MBL concentration between the HIV positive and HIV negative individuals, consistent with other reports [ 80 82 ]. In contrast, some have reported protective effect of normal plasma MBL levels and increased susceptibility due to low MBL levels [ 30 , 37 , 83 , 84 ], but some reported a deleterious effect of normal plasma MBL levels where high MBL levels were associated with acquiring HIV infection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three genetic studies of Chinese populations have demonstrated that MBL deficiencies are associated with increased susceptibility to HIV-1 infection and disease progression (Sheng et al, 2010) (Tan et al, 2009) (Li et al, 2013) and serum circulating levels of normal MBL in HIV-1-infected patients could be an important auxiliary biological marker in association with CD4(+) T cell counts in the evaluation of HIV-1 disease progression (Tan et al, 2009). These findings are consistent with studies previously conducted by Dzwonek et al (2006) in the UK (Dzwonek et al, 2006).…”
Section: Complement Activation In Hiv-infectionmentioning
confidence: 99%
“…Η ίδια ομάδα ερευνητών βρήκε σημαντικά χαμηλότερα επίπεδα MBL σε ασθενείς με HIV λοίμωξη σε σχέση με τους μάρτυρες στην υπο-Σαχάριο Αφρική408 . Επόμενες μελέτες σε άλλους πληθυσμούς έδειξαν παρόμοια αποτελέσματα[409][410][411][412] . Μία τουλάχιστον μελέτη δεν βρήκε καμία συσχέτιση413 ενώ μια μεγάλη έρευνα ασθενών μαρτύρων 414 έδειξε αντίστροφα ευρήματα.…”
unclassified